European research on education and training : FP6 and FP7 research projects addressing directly issues of education and training. EUR 23865 EN (Luxembourg, 2009)
"High quality education and training systems are essential for European welfare and for developing a knowledge-based society. This publication aims to give an overview of the European research carried out in the 6th and 7th Framework Programmes. These education and training projects deal with knowledge and skills (Lisbon Strategy), inclusion and cohesion (Social Agenda), culture, youth and migration (Citizenship), horizontal, international and support actions."